Incorporating Clinical Experiences at a Community-Based Free Clinic to Improve Nursing Students' Understanding of Rural, Medically Underserved Populations - Michelle Cheshire; Michele Montgomery; Paige Johnson (Rural Nurse Organization; Binghamton University, 2017)
Schools of nursing have a responsibility to incorporate content related to social determinants of health and rural health into their curriculum and reinforce this content by providing nursing students with clinical experiences in which they can gain hands on experience providing care to rural residents. Free clinics provide a vital service to underserved, rural communities, but often remain an underutilized site for nursing clinical education. The partnership between a free clinic in west Alabama and one school of Nursing has demonstrated that students gain valuable insight not only into the health care needs of rural populations, but also the value of interprofessional collaboration to provide health services to this population. This clinical experience provided an avenue for students to meet their clinical objectives and serve a population of rural residents that were invested in their health but needed the services of this free clinic. Senior level BSN students in the Community Health Nursing course assigned to this clinical site reported an intention to serve rural, medically underserved populations after graduation. Keywords: Rural populations, Nursing education, Medically underserved populations DOI:  http://dx.doi.org/10.14574/ojrnhc.v17i1.439